2012
DOI: 10.1007/s13280-012-0331-0
|View full text |Cite
|
Sign up to set email alerts
|

An Index to Determine Vulnerability of Communities in a Coastal Zone: A Case Study of Baler, Aurora, Philippines

Abstract: A coastal community vulnerability index (CCVI) was constructed to evaluate the vulnerability of coastal communities (Buhangin, Pingit, Reserva, Sabang, and Zabali) in the municipality of Baler, Aurora, Philippines. This index was composed of weighted averages of seven vulnerability factors namely geographical, economic and livelihood, food security, environmental, policy and institutional, demographic, and capital good. Factor values were computed based on scores that described range of conditions that influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 19 publications
0
31
0
1
Order By: Relevance
“…In many cases, particularly where statistical data are unavailable, unreliable, or incomplete, processes of data collection have been more participatory. Experts and local stakeholders have been engaged to identify indicators, to design indices, to incorporate local knowledge of hazard and vulnerability conditions, to provide weights for indicators, and to ensure appropriateness to local contexts (e.g., Huang et al 2012;Kienberger 2012;Orencio and Fujii 2012;Torresan et al 2012). After developing a SoVItype index using statistical data, Oulahen et al (2015) engaged municipal government staff in several Canadian municipalities to validate, weight, and revise it.…”
Section: Vulnerability and Risk Indicatorsmentioning
confidence: 99%
“…In many cases, particularly where statistical data are unavailable, unreliable, or incomplete, processes of data collection have been more participatory. Experts and local stakeholders have been engaged to identify indicators, to design indices, to incorporate local knowledge of hazard and vulnerability conditions, to provide weights for indicators, and to ensure appropriateness to local contexts (e.g., Huang et al 2012;Kienberger 2012;Orencio and Fujii 2012;Torresan et al 2012). After developing a SoVItype index using statistical data, Oulahen et al (2015) engaged municipal government staff in several Canadian municipalities to validate, weight, and revise it.…”
Section: Vulnerability and Risk Indicatorsmentioning
confidence: 99%
“…However, we have to acknowledge that the quality of the survey instrument always affects data resulting from this approach. Such quality includes the steps undertaken to develop the tool [26] and their limited spatial and temporal applications [27].…”
Section: Questionnaire Surveysmentioning
confidence: 99%
“…However, we observed that this could also be challenging due to the unavailability of reliable and pertinent data. In this case, gathering responses at the household level and quantifying them based on a scale to gauge conditions has been substantial in the process of indicator-based assessment [26].…”
Section: Integrated Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite criticisms concerning the use of indicators, their local relevance is widely supported (Barnett et al 2008;Orencio and Fujii 2013). In this paper, we conceptualise vulnerability as a theoretical, non-observable phenomenon that relates to the propensity of a system, subsystem or system component to experience harm due to exposure to a perturbation or stressor (Turner et al 2003).…”
Section: Theoretical Background Indicator-based Vulnerability Assessmentmentioning
confidence: 99%